Bulgaria : Household Welfare during the 2010 Recession and Recovery - World Bank (Washington, DC, 2013)
This report assesses the impact of the 2009 recession and the fragile recovery of 2010 on the welfare of Bulgarian households and the effectiveness of Government policies in mitigating its costs. By the beginning of 2009, the global economic crisis had affected much of Europe, including Bulgaria. The output decline lasted five quarters, followed by a modest increase during the rest of 2010. However, despite the large fluctuation in output during 2009-10, households preserved their 2008 income level throughout this period. What lies behind this example of successful income smoothing amid a large regional and national recession? Which were the key transmission channels through which the macro crisis filtered through to the household level? What population groups were most affected? What was the role played by public policy in mitigating the impact of the crisis? What lessons can be learned from the Bulgarian experience on protecting households during a crisis, while maintaining prudent fiscal and macroeconomic policies? To answer these questions, the report uses an exceptionally rich survey to assess how households were impacted, how they responded to the crisis and how/if they benefited from a comprehensive government policy package.